English language use and attitude of international Chinese students in Malaysia / Ning Jing - Ning , Jing (2023)

(untitled)
The choice of Chinese university students' language attitudes as the research topic stems from language contact and language competition in China's rapid development. China is one of the countries with the most language assets. The researcher has determined from these phenomena that Chinese people have different opinions about English and its use and attitudes. Language attitude reflects social psychology, which is people's feelings and evaluations of language variants of a particular language or dialect. The study of language attitude is a subject of theoretical value in sociolinguistics and great practical value in understanding the psychological characteristics of a nation, a group, or an association. Therefore, in this study, the researcher found that there is a low level of English language use among Chinese university students in Malaysia. In comparison, Chinese university students have a moderate attitude towards the English language.Furthermore, the researcher also found out that there is a significant relationship between English language use and attitude towards English among Chinese university students, which the previous studies have not included. In order to have detailed knowledge regarding this topic, the researcher has analyzed the significant difference between all five variables and English language use and attitude. Findings show that only one age group has a significant difference in English language use among Chinese university students in Malaysia.